Stemness Phenotype in Tamoxifen Resistant Breast Cancer Cells May be Induced by Interactions Between Receptor Tyrosine Kinases and ERα-66 - Farahmand, Leila; Mansouri, Sepideh; Jafarbeik-Iravani, Narges; Teymourzadeh, Azin; Majidzadeh-A, Keivan (Recent Patents on Anti-Cancer Drug Discovery, 2018)
Background: Tamoxifen is widely administered for patients with estrogen receptor-positive breast cancer. Despite many patients benefiting from Tamoxifen as an effective anti-hormonal agent in adjuvant therapy, a noticeable number of patients tend to develop resistance. Objective: The aim of this study was to shed light upon the molecular mechanisms associated with Tamoxifen resistance which can help improve current treatment strategies available for stimulating responsiveness and combating resistance. Methods: Relevant articles were obtained from PubMed and google scholar, nearly all dated from 2010 to 2017. Articles were screened to select the ones meeting the objective. The molecular interactions in the resistant network were extracted from the appropriate articles. Results: The mechanisms of developing Tamoxifen resistance were briefly outlined. Overactivation of Receptor Tyrosine Kinases (RTKs) pathways, commonly known as alternative growth cascades, is one of the main players in acquired cancer cell stemness, which can induce unrestricted proliferation in the presence of Tamoxifen. There are seven recent patents including 6291496B1 as an anti-HER2, 8143226B2 as an inhibitor of RTK phosphorylation, 9062308B2 as an anti-HOXB7, Lapatinib functioning as an anti-EGFR/HER2, Everolimus as an inhibitor of mTOR, Exemestane as an aromatase inhibitor and Perifosine as an AKT inhibitor. Conclusion: Altogether, it seems that tumor cells express a stemness phenotype which tends to override anti-hormonal adjuvant therapies. Since RTKs are overactivated and overexpressed in such cells, specialized targeted therapies suppressing RTKs would be a novel and effective way in restoring Tamoxifen sensitivity in resistant breast cancer tumor cells.
Keywords: stemness phenotype